Expresión xz∨¬x¬z∨¬y¬z∨¬xy∨x¬y
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(x∧z)∨(x∧¬y)∨(y∧¬x)∨(¬x∧¬z)∨(¬y∧¬z)=(x∧z)∨(x∧¬y)∨(y∧z)∨(y∧¬x)∨(¬x∧¬z)∨(¬y∧¬z)
(x∧z)∨(x∧¬y)∨(y∧z)∨(y∧¬x)∨(¬x∧¬z)∨(¬y∧¬z)
(x∧z)∨(y∧z)∨(x∧(¬y))∨(y∧(¬x))∨((¬x)∧(¬z))∨((¬y)∧(¬z))
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 1 |
+---+---+---+--------+
| 1 | 0 | 1 | 1 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(x∧z)∨(x∧¬y)∨(y∧z)∨(y∧¬x)∨(¬x∧¬z)∨(¬y∧¬z)
(x∧z)∨(y∧z)∨(x∧(¬y))∨(y∧(¬x))∨((¬x)∧(¬z))∨((¬y)∧(¬z))
(x∨y∨¬z)∧(z∨¬x∨¬y)∧(x∨y∨z∨¬z)∧(x∨y∨¬x∨¬y)∧(x∨y∨¬x∨¬z)∧(x∨y∨¬y∨¬z)∧(x∨z∨¬x∨¬y)∧(x∨z∨¬x∨¬z)∧(y∨z∨¬x∨¬y)∧(y∨z∨¬y∨¬z)∧(z∨¬x∨¬y∨¬z)∧(x∨y∨z∨¬x∨¬y)∧(x∨y∨z∨¬x∨¬z)∧(x∨y∨z∨¬y∨¬z)∧(x∨y∨¬x∨¬y∨¬z)∧(x∨z∨¬x∨¬y∨¬z)∧(y∨z∨¬x∨¬y∨¬z)∧(x∨y∨z∨¬x∨¬y∨¬z)
(x∨y∨(¬z))∧(z∨(¬x)∨(¬y))∧(x∨y∨z∨(¬z))∧(x∨y∨(¬x)∨(¬y))∧(x∨y∨(¬x)∨(¬z))∧(x∨y∨(¬y)∨(¬z))∧(x∨z∨(¬x)∨(¬y))∧(x∨z∨(¬x)∨(¬z))∧(y∨z∨(¬x)∨(¬y))∧(y∨z∨(¬y)∨(¬z))∧(z∨(¬x)∨(¬y)∨(¬z))∧(x∨y∨z∨(¬x)∨(¬y))∧(x∨y∨z∨(¬x)∨(¬z))∧(x∨y∨z∨(¬y)∨(¬z))∧(x∨y∨(¬x)∨(¬y)∨(¬z))∧(x∨z∨(¬x)∨(¬y)∨(¬z))∧(y∨z∨(¬x)∨(¬y)∨(¬z))∧(x∨y∨z∨(¬x)∨(¬y)∨(¬z))
Ya está reducido a FND
(x∧z)∨(x∧¬y)∨(y∧z)∨(y∧¬x)∨(¬x∧¬z)∨(¬y∧¬z)
(x∧z)∨(y∧z)∨(x∧(¬y))∨(y∧(¬x))∨((¬x)∧(¬z))∨((¬y)∧(¬z))
(x∨y∨¬z)∧(z∨¬x∨¬y)